2023
DOI: 10.1038/s41541-023-00615-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjuvants in a rabies-vectored Ebola virus vaccine on protection from surrogate challenge

Abstract: Ebola virus is the primary contributor to the global threat of filovirus severe hemorrhagic fever, and Ebola virus disease has a case fatality rate of 50–90%. An inactivated, bivalent filovirus/rabies virus vaccine, FILORAB1, consists of recombinant rabies virus virions expressing the Ebola virus glycoprotein. FILORAB1 is immunogenic and protective from Ebola virus challenge in mice and non-human primates, and protection is enhanced when formulated with toll-like receptor 4 agonist Glucopyranosyl lipid adjuvan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…It is found in various bodily secretions and tissues, including blood, tears, and saliva [21]. Adjuvants can activate the nonspeci c immune cells, such as macrophages and dendritic cells, leading to the production of various immune mediators and cytokines [22,23]. In this study, lysozyme activity increased several folds in the AE adjuvanted sh.…”
Section: Discussionmentioning
confidence: 60%
“…It is found in various bodily secretions and tissues, including blood, tears, and saliva [21]. Adjuvants can activate the nonspeci c immune cells, such as macrophages and dendritic cells, leading to the production of various immune mediators and cytokines [22,23]. In this study, lysozyme activity increased several folds in the AE adjuvanted sh.…”
Section: Discussionmentioning
confidence: 60%
“…Five C3H/HeN mice per group were immunized with 10 4 foci-forming units (ffu) of live BNSP333-BBI39 or BNSP333-BBI39 RVG . Since BNSP33-BBI39 RVG incorporates BBI39 into the virion, we also tested it as an inactivated vaccine, both with and without the adjuvant PHAD-SE [ 24 ]. Several studies have demonstrated that PHAD-SE induces a Th1-biased immune response [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since BNSP33-BBI39 RVG incorporates BBI39 into the virion, we also tested it as an inactivated vaccine, both with and without the adjuvant PHAD-SE [ 24 ]. Several studies have demonstrated that PHAD-SE induces a Th1-biased immune response [ 24 , 25 ]. This should induce borreliacidal antibodies that can bind, complement, and protect against Borrelia burgdorferi , as shown in other studies [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations